2019
DOI: 10.1016/j.bbi.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early life stress on cocaine conditioning and AMPA receptor composition are sex-specific and driven by TNF

Abstract: Exposure to early life adversity can predispose adolescents to the formation of substance abuse disorders. In rodents, early stressors such as repeated maternal separation (MS) impact AMPAR activity in the prefrontal cortex (PFC) and nucleus accumbens (NAc), regions involved in drug-cue association after cocaine-induced conditioned place preference (CPP). Notably, previous reports suggest that the pro-inflammatory cytokine tumor necrosis factor (TNF) regulates AMPAR subunit composition; increased TNF levels ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 60 publications
9
33
0
Order By: Relevance
“…Therefore, our results support early life adversity as a critical non-genetic risk factor for the development of drug-related problems during adolescence. These findings add relevant data to the, so far, scarce literature suggesting that MS causes alterations that influence vulnerability to drug abuse in adolescent rodents [19][20][21] . In previous studies, also using CPP, Ganguly and colleagues 19 (MS for 4 h daily, PND 2-20) and Viola and colleagues 21 (MS for 3 h daily, PND 2-15) showed that MS in adolescent male rodents, but not in female, lead to a preference for the drug paired compartment.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, our results support early life adversity as a critical non-genetic risk factor for the development of drug-related problems during adolescence. These findings add relevant data to the, so far, scarce literature suggesting that MS causes alterations that influence vulnerability to drug abuse in adolescent rodents [19][20][21] . In previous studies, also using CPP, Ganguly and colleagues 19 (MS for 4 h daily, PND 2-20) and Viola and colleagues 21 (MS for 3 h daily, PND 2-15) showed that MS in adolescent male rodents, but not in female, lead to a preference for the drug paired compartment.…”
Section: Discussionsupporting
confidence: 67%
“…These findings add relevant data to the, so far, scarce literature suggesting that MS causes alterations that influence vulnerability to drug abuse in adolescent rodents [19][20][21] . In previous studies, also using CPP, Ganguly and colleagues 19 (MS for 4 h daily, PND 2-20) and Viola and colleagues 21 (MS for 3 h daily, PND 2-15) showed that MS in adolescent male rodents, but not in female, lead to a preference for the drug paired compartment. Other authors, using the maternal deprivation paradigm (MS for 24 h, PND12/13) showed increased anxiety in adolescents, but with impaired motivation for cocaine 20 .…”
Section: Discussionsupporting
confidence: 67%
“…However, we did not observe significant 413 differences in GluA1 or GluA2 protein level in MSEW exposed mice. Our results are in 414 accordance with Ganguly et al (2019) who reported that males maternally separated 415 showed decreased in mPFC-Gria2 expression compared to control males. Likewise, they 416 observed that females in general, showed higher GluA2 protein level than male mice, 417 similar to our findings.…”
supporting
confidence: 89%
“…In addition, we have previously shown the importance of the dorsal hippocampus (Fakira et al, 2016;Williams et al, 2019) and AMPAR signaling in the modulation of opioid-associated contextual memory (Morón et al, 2007;Billa et al, 2009;Billa et al, 2010;Xia et al, 2011). Sex differences in AMPAR activity have also been linked to cocaine-associated memory (Bechard et al, 2018;Ganguly et al, 2019). Therefore, the novel component of sex differences in spatial memory identified here suggest that CNIH3 could play a role in sex-dependent drug-associated memory.…”
Section: Discussionmentioning
confidence: 56%